Issues of genre and literary influences in the contemporary Croatian cinema - Gilić, Nikica (2012)
Contemporary Croatian cinema, with a conspicuos exception of the first "hit" in the post-Yugoslav Croatian cinema ("How the war started on my island"/"Kako je počeo rat na mom otoku"), practically all succesful Croatian productions were based on Croatian contemporary literature - novels and short stories collections. Even the more succesful promotional activities for recent Croatian feature films are based precisely on the literary sources and popular (media) narratives about them, quite contrary to the expected larger popularity factor of the cinema medium. This is very obvious in the cases of films such as Hrvoje Hribar's "What's a man without a moustache" ("Što je muškarac bez brkova") and Danijel Kušan's "koko and the ghosts" ("Koko i duhovi"), as well as Branko Schmidt's films based on Alen Bović's (Ivo Balenović's) novels.
Projekt MZOS
ENG